2022
DOI: 10.1177/24730114221115689
|View full text |Cite
|
Sign up to set email alerts
|

Initial Impact of the COVID-19 Pandemic on a US Orthopaedic Foot and Ankle Clinic

Abstract: Background: In the United States, the COVID-19 pandemic led to a nationwide quarantine that forced individuals to adjust their daily activities, potentially impacting the burden of foot and ankle disease. The purpose of this study was to compare diagnoses made in an orthopaedic foot and ankle clinic during the shelter-in-place period of the COVID-19 pandemic to diagnoses made during the same months of the previous year. Methods: A retrospective review of new patients presenting to the clinics of 4 fellowship-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In the first year of COVID-19, the incidence of surgical fractures in Sao Paulo city decreased, as did the lower limb surgical fractures. The reduction may be due to the isolation applied in the city that reduced the chance of high-energy traumas such as automobile accidents, falls from great heights, or sports traumas (16,17) . This decrease in incidence was seen in most studies that described the initial phase of COVID-19 (8)(9)(10)(11)(12)(13)16,17) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first year of COVID-19, the incidence of surgical fractures in Sao Paulo city decreased, as did the lower limb surgical fractures. The reduction may be due to the isolation applied in the city that reduced the chance of high-energy traumas such as automobile accidents, falls from great heights, or sports traumas (16,17) . This decrease in incidence was seen in most studies that described the initial phase of COVID-19 (8)(9)(10)(11)(12)(13)16,17) .…”
Section: Discussionmentioning
confidence: 99%
“…The reduction may be due to the isolation applied in the city that reduced the chance of high-energy traumas such as automobile accidents, falls from great heights, or sports traumas (16,17) . This decrease in incidence was seen in most studies that described the initial phase of COVID-19 (8)(9)(10)(11)(12)(13)16,17) . However, malleolar and talar fractures, considered high-energy trauma, increased during this period and may be associated with changes in patient habits during the isolation period.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective review of new patients in the city of Chicago reported a significantly higher proportion of ankle fractures and stress fractures than those during the same months before the COVID-19 pandemic. 15 As there are no epidemiological studies available on Japanese collegiate men's basketball players during the COVID-19 pandemic, the purpose of the current study was to describe the incidence of lower extremity injuries in this population during 2 seasons affected by the pandemic (2020-21 and 2021-22). Lower extremity injuries were chosen, as they have been reported as the most frequent in basketball.…”
mentioning
confidence: 99%
“… 19 Several studies have reported the effects of the COVID-19 pandemic on lower extremity injuries. 4 , 15 , 16 , 19 Demir et al 4 showed the risk for muscle injuries due to long-term detraining by COVID-19 confinement in professional soccer players. A retrospective review of new patients in the city of Chicago reported a significantly higher proportion of ankle fractures and stress fractures than those during the same months before the COVID-19 pandemic.…”
mentioning
confidence: 99%
See 1 more Smart Citation